A Chronicle of resilience : management practices in meeting the challenges on the shift in educational setup - Nava, Joel B. (Saint Louis College, City of San Fernando, La Union : [s.n.], 2023)
This study sought to investigate how school administrators handled the issues associated with the transition from a modular to face-to-face learning environment in the First Congressional District of La Union's Medium, Large, and Mega Large 12 Public Secondary Schools as the foundation for developing a thematic model. In this investigation, transcendental phenomenology was used. Data was gathered through a one-on-one interview with the 12 principals of the participating schools for the school year n2022-2023. It was found that continuing professional development, maintaining safe and motivating, learning environment, setting budget on priorities, and strengthening monitoring and supervision were the innovative practices implemented by the school heads in the new normal education. It was concluded that the school heads work and embrace relentlessly the implementation of innovative practices to provide human, financial, material, and instructional support for teachers to achieve quality instruction as a way of exemplifying their efficiency and educational leadership in the new normal. The thematic model crafted by the researcher can be used as guide in executing the roles of the school heads to improve quality of teaching and learning in the First Congressional District of La Union.
References: pages 82-88.
CHED-La Union
Keywords: School -- Administration